Neurofibromatosis 1, Thalamic Hyperintensities, and Cognitive Impairment - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
The relationship between T2 weighted MRI images (T2H) and cognitive functioning in a cohort of 76 children with neurofibromatosis type 1 (NF1) was determined in a study at Children's Hospital at Westmead, University of Sydney, Australia.